Caracterização estrutural e evolução de osmóforos e nectários em Spiranthinae lindl. ex meisn. (Orchidaceae) - Maria Letícia Neves Figueiredo (2018)
Osmophores and nectaries are essential components in orchid flowers, being associated with the high specialization of pollination in the family. In Spiranthinae, the presence of osmophores was described for the abaxial aspect of the lip, an unusual location in orchid flowers. In this subtribe, the nectar storage region is essentially delimited by the base of the lip, the foot of the column and the lateral sepals. Studies, mainly of floral biology, indicate the presence of nectar producing auricles at the base of the lip, in lateral projections or swellings with glandular cells, in several species of the group. The general structure of Spiranthinae flowers indicates that the syndrome of melittophily is the most common and widely distributed in the group. Alternatives to melittophily seem to demonstrate an adaptive irradiation in the subtribe for several groups of pollinators (moths, butterflies and hummingbirds), probably from an ancestral melittophilic condition. As a result of the wide variation observed in the Spiranthinae pollination syndromes and the unusual structures of the nectars and osmophores already observed for the group, this work describes the morphology and anatomy of osmophors and floral nectaries in species of different lineages of the subtribe to associate the occurrence and characteristics of these secretory structures with pollination mechanisms and groups of pollinators and their evolution in the group. Flowers of individuals belonging to 17 species of the Cranichideae tribe (14 Spiranthinae and three of its sister group, Cranichidinae) were collected and morphological, light microscopy, transmission and scanning analysis were performed, as well as multivariate morphometric analysis and optimization of structural characters for parsimony. The results indicate that the auricles found at the base of the lip are effectively nectaries, and that the most common position of the osmophores in the subtribe is the abaxial surface of the lip. In the dendrogram constructed from the matrix with all the characters there are few well defined groups, due to the low general similarity between the species. A first division in the dendrogram separates all species of Spiranthinae in one group and the species of Cranichidinae constituting another group. The only group formed entirely by and including all species exhibiting the same pollination syndrome is the ornithophilous species, which appears as the most cohesive and differentiated in the analysis using only the anatomical characters. None of the groups mentioned in the analysis using only the anatomical characters was retrieved in the analysis employing the matrix with only the morphological characters, and the latter did not reflect both the pollination syndromes and the phylogeny of the group. All anatomical characters presented some degree of homoplasy, which eventually was elevated. In general, very little correlation was observed between the evolution of these characters and the phylogeny of the group or the pollination syndromes. Notable exceptions are related to ornithophily and pollination by pollinators with long buccal apparatus, and eventual synapomorphies of main clades.